2002
DOI: 10.1140/epjb/e20020025
|View full text |Cite
|
Sign up to set email alerts
|

Advanced memory effects in the aging of a polymer glass

Abstract: A new kind of memory effect on low frequency dielectric measurements on plexiglass (PMMA) is described. These measurements show that cooling and heating the sample at constant rate give an hysteretic dependence on temperature of the dielectric constant ǫ. A temporary stop of cooling produces a downward relaxation of ǫ. Two main features are observed i) when cooling is resumed ǫ goes back to the values obtained without the cooling stop ( i.e. the low temperature state is independent of the cooling history) ii) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 17 publications
7
42
1
Order By: Relevance
“…This is not totally unexpected, as we already know experimentally that systems quite different from spin glasses show memory and rejuvenation. [12][13][14][15][16] The natural conclusion is that chaos, although probably present in realistic spin glasses, 34,38,47 need not be invoked to explain memory and rejuvenation. However, it has been argued 11 that the experimental protocol introduced in Ref.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is not totally unexpected, as we already know experimentally that systems quite different from spin glasses show memory and rejuvenation. [12][13][14][15][16] The natural conclusion is that chaos, although probably present in realistic spin glasses, 34,38,47 need not be invoked to explain memory and rejuvenation. However, it has been argued 11 that the experimental protocol introduced in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…This was maybe to be expected, since memory and rejuvenation is being found experimentally in materials where chaos in temperature seems to be absent or where a thermodynamic glass transition has never been found. [12][13][14] Unfortunately, we have made no progress 39 in the analysis of the dip-experiment protocol.…”
Section: ͑1͒mentioning
confidence: 99%
See 1 more Smart Citation
“…On subsequent reheating the ac susceptibility shows a dip around each aging temperature -the system has kept a memory of each equilibration at constant temperature. The memory experiment is an efficient tool to study spin-glass-like properties in various materials [114][115][116][117][118]. For the Ag(11 at% Mn) sample, the ac susceptibility curve measured on cooling lies below the curve subsequently measured on heating, except close to the lowest temperature (see Fig.…”
Section: Experiments: Aging Memory and Rejuvenationmentioning
confidence: 99%
“…This temperature cycling protocol has been used extensively to characterize several spin glass systems 2,3,4,5,6,7,8,9,10,11,12,13,14,15 , and these studies motivated similar cycling experiments on many different types of glassy materials 16,17,18,19,20,21,22,23,24,25 . Numerical studies of temperature shifts and cycles in the Ising version of the model have been reported 26,27,28,29,30,31,32,33 , and temperature cycles have been discussed theoretically 34,35,36,37,38,39,40,41,42 .…”
Section: Introduction To Basic Phenomenamentioning
confidence: 99%